Classical Hodgkin lymphoma histologic subtypes distribution among geographical regions and correlation with Human Development Index - Alberto Moscona-Nissan; María Fernanda Mancilla-Osuna; Andrea Bardán-Duarte; Mario Enrique Rendón-Macías (Health Sciences Review, 2023)
Classical Hodgkin lymphoma (cHL) is classified into nodular sclerosis (NS), mixed cellularity (MC), lymphocyte rich (LR), and lymphocyte depleted (LD) histologic subtypes. Epidemiologic studies demonstrate remarkable diversity of subtype distribution among geographical regions and socioeconomic conditions. However, previous research has not examined the statistical correlation between subtypes’ proportion of cases among countries and socioeconomic factors, reported through a standardized parameter as the Human Development Index (HDI). Our aim was to analyze cHL histologic subtypes' frequency patterns among geographic regions and establish a correlation with countries' socioeconomic conditions.We conducted a systematic review in national registries, population-based reports and multicenter studies addressing histologic subtype frequency in different countries from 1980 to 2021. We evaluated 26,174 cHL patients from 27 countries among five geographic regions. For each cHL subtype, we calculated the Pearson correlation coefficient, determination coefficient and created scatter plots.North and Central America and Europe were the regions with the highest overall proportion of NS cases, while East and South Asia and Africa had the highest proportion of MC and LD cases. A significant positive correlation was confirmed between NS proportion of cases among countries and a higher HDI (R2=0.33, r = 0.57, p<0.001). Conversely, a negative correlation was found between MC and LD subtype proportion of cases and a higher HDI (R2=0.35, r=-0.59, p<0.001 for MC and R2=0.08, r=-0.29, p>0.05 for LD). LR subtype distribution showed no correlation with HDI (R2 <0.00001, r = 0.002, and p>0.05).Early Epstein-Barr virus infection, host-related factors (as an altered immune response, nutritional status), human immunodeficiency virus infection, among other factors could explain these differences. Understanding cHL distribution patterns and their underlying causes, could allow to create public health interventions to improve social determinants of health in developing countries.